IDENTIFIKASI TINGKAT KENYAMANAN LINGKUNGAN KERJA FISIK PADA CHEF BURJO BORNEO TERHADAP SUHU UDARA - Alex Alfandianto; Inaaratul Chusna Ichda Purwanto; Aldi Yoga Pradana (Universitas Islam Nahdlatul Ulama Jepara, 2019)
In general, people spend more than 90% of the time in the room, so they need a comfortable air in the space where they move, therefore the good indoor air velocity is very beneficial to them. Resolving indoor comfort issues is possible through a thorough research based on the air velocity in the cooking room. The analysis of the physical work environment of the cooking room of Burjo Borneo, the researcher will give the output or the result of the relationship of air temperature influence to the convenience of cooking operator, therefore, work and effort can be done to cooking operator to cook and serve food, the negative impacts arising from the problem. Air temperature to comfort level, it is known that the minimum temperature with an average of 29.300 C and a maximum temperature of 30,500 C gives the amount of discomfort much higher than the air quality level. This is because during breaks to cook and serve food, cooking operators hard to concentrate on doing activities. It was found that the factors of discomfort and the temperature of the hot air into the treatment that caused the feeling uncomfortable. This is because in hot temperatures, cooking operators experience rapid sweat excretion.